2003
DOI: 10.1002/jlcr.790
|View full text |Cite
|
Sign up to set email alerts
|

Ligand effects upon deuterium exchange in arenes mediated by [Ir(PR3)2(cod)]+.BF4

Abstract: SummaryA series of complexes of general form [Ir(PR 3 ) 2 (cod)] + has been prepared and used, without isolation, to mediate deuteration of a range of model substrates. The data suggest that, with many substrates, basicity of the phosphine ligands bound to iridium is an important factor influencing substrate selectivity and the efficiency of deuteration. In addition, the spectrum of activity of iridium complexes bearing pure donor ligands is different in many cases to that of complexes where the ligands are kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…We have already demonstrated that the effect of the phosphine cone angle in 2 and its analogues is small so that, in this series, the principal effect of changing the nature of the arsine ligand should be electronic. 11 However, exchange into phenylacetone in the presence of complexes 3 was not improved by modifying the ligands, systems other than 3a mediating no more than 25% of the theoretical maximum level of exchange.…”
Section: Exchange Using Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…We have already demonstrated that the effect of the phosphine cone angle in 2 and its analogues is small so that, in this series, the principal effect of changing the nature of the arsine ligand should be electronic. 11 However, exchange into phenylacetone in the presence of complexes 3 was not improved by modifying the ligands, systems other than 3a mediating no more than 25% of the theoretical maximum level of exchange.…”
Section: Exchange Using Complexesmentioning
confidence: 99%
“…Electronic effects will also be different to those observed in complexes of simple phosphines; the distortion caused by chelate formation increases the basicity of the metal centre, 10 this effect increasing as the size of the chelate ring decreases. Since iridium complexes of the most basic phosphines are of limited value, 11 it was expected that the best results would be obtained using complexes with bis(phosphines) of moderate basicity. Indeed, the results presented in Table 1 are broadly in line with this expectation.…”
Section: Exchange Using Complexesmentioning
confidence: 99%
“…Early catalyst inactivation would explain the poor correlation between ligand properties and the level of isotopic exchange for substrates whose binding kinetics are unfavourable or where initial exchange is slow. 7 …”
Section: Introductionmentioning
confidence: 99%
“…The same deuteration pattern has earlier been reported using rhodium(III) hydride complexes but with lower level of deuterium incorporation (9%) in the pyridine ring. 11 Ellames et al 12 has investigated the use of iridium based catalysts of the general form [Ir(PR 3 ) 2 (COD)]…”
Section: Resultsmentioning
confidence: 99%